Evaluation of Jakarta Province in Information and Technology Management (Jurnal Bina Praja, 2022)
Electronic government has become an important issue in Indonesia's bureaucratic reform. Aside from the big-bang decentralization policy, e-govt has endorsed national concerns to digitize the rigid manual procedures of public services. Jakarta, as the capital city, emphasizes IT- the backbone of administration. IT is yet widely used by Jakarta to get a new shape in Jakarta's capabilities and capacities. Over two decades, passing different governors, Jakarta persistent injected IT into public administration, launching integrated IT applications to present a smart city. Despite the award of Jakarta digital services, Jakarta IT management should be evaluated. The approach used in the research to examine the symptoms of the object of study is a mixed-method approach with a sequential model. The informant selection technique uses purposive sampling. Informants' selection process by adjusting the business processes in COBIT 2019 using the RACI Chart method. The data analysis techniques used Guttman Scale. The result shows the appropriate business processes are: APO02 (managed strategy), APO03 (driven architecture), BAI05 (managed organizational change), and DSS06 (managed business process control). The study results show that the capability level is t of 4 scales as a target. The gap value of 0.25 indicates that technology and information management have been implemented and running well, but each business process needs improvement to reach the maximum level. Despite the gap between as-is and to-be, Jakarta's capability level is impressive. It reflects the persistent injection of IT with adequate support. The Jakarta province needs to pay attention to software and hardware compatible with the organization's vision and improve coordination among divisions. Training, staffing, dispatching, and rotating need qualified human resources to enhance organizational performance. DKI Jakarta Province also needs routine monitoring, evaluating problems, and documenting all business processes as a source of information.
Keywords: IT governance audit; COBIT 2019; information technology; maturity level